Proteomic Analysis of the Venom of Jellyfishes Rhopilema esculentum and Sanderia malayensis - Thomas C. N. Leung; Zhe Qu; Wenyan Nong; Jerome H. L. Hui; Sai Ming Ngai (Marine Drugs, 2020)
Venomics, the study of biological venoms, could potentially provide a new source of therapeutic compounds, yet information on the venoms from marine organisms, including cnidarians (sea anemones, corals, and jellyfish), is limited. This study identified the putative toxins of two species of jellyfish—edible jellyfish Rhopilema esculentum Kishinouye, 1891, also known as flame jellyfish, and Amuska jellyfish Sanderia malayensis Goette, 1886. Utilizing nano-flow liquid chromatography tandem mass spectrometry (nLC–MS/MS), 3000 proteins were identified from the nematocysts in each of the above two jellyfish species. Forty and fifty-one putative toxins were identified in R. esculentum and S. malayensis, respectively, which were further classified into eight toxin families according to their predicted functions. Amongst the identified putative toxins, hemostasis-impairing toxins and proteases were found to be the most dominant members (>60%). The present study demonstrates the first proteomes of nematocysts from two jellyfish species with economic and environmental importance, and expands the foundation and understanding of cnidarian toxins.